Characteristic analysis on an interleaver with a fiber loop resonator by using a signal flow graph method - Li, Weibin; Sun, Junqiang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
We propose an interleaver based on the Mach–Zehnder interferometer with a resonator incorporated in one arm. By using the method of signal flow graph, we get the simple closed-form expressions for transmission of this interleaver. The result indicates that the widths of 0.5 dB passband and 25 dB stopband of the interleaver are improved remarkably, which are much wider than that of the conventional Mach–Zehnder interferometer. The interleaver proposed has an ideal rectangular spectral response. Finally, we have analyzed the influence exerted by the parameters on its transimission characteristics and found that the transmission spectrum of this device depends highly on the intensity coupling coefficient of the coupler and fiber loop length.
Optica Applicata, Vol. 38, 2008, nr 3, s. 503-510
Keywords: optyka; interleaver; resonator; signal flow graph; transmission